2011
DOI: 10.3389/fnins.2011.00060
|View full text |Cite
|
Sign up to set email alerts
|

Towards Intelligent Environments: An Augmented Reality–Brain–Machine Interface Operated with a See-Through Head-Mount Display

Abstract: The brain–machine interface (BMI) or brain–computer interface is a new interface technology that uses neurophysiological signals from the brain to control external machines or computers. This technology is expected to support daily activities, especially for persons with disabilities. To expand the range of activities enabled by this type of interface, here, we added augmented reality (AR) to a P300-based BMI. In this new system, we used a see-through head-mount display (HMD) to create control panels with flic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 25 publications
6
36
0
Order By: Relevance
“…The classification accuracy tended to confirm our hypothesis as all of the conditions' classification accuracy were between 75% and 80% which is consistent with the literature [15], [16]. It also confirms the previous results of Takano et al [14] on the possibility to combine AR and BCI headsets.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The classification accuracy tended to confirm our hypothesis as all of the conditions' classification accuracy were between 75% and 80% which is consistent with the literature [15], [16]. It also confirms the previous results of Takano et al [14] on the possibility to combine AR and BCI headsets.…”
Section: Resultssupporting
confidence: 93%
“…The use of BCIs has been less explored in the context of OST-AR. To the authors' best knowledge, only Takano et al [14] have explicitly explored this solution. Their study evaluated a home automation system in two steps.…”
Section: Optical See-through Ar and Bcimentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that similar and satisfactory accuracies (76–88%) can be achieved with a see-through HMD as compared to an LCD monitor (Takano et al, 2011 ). In their study, participants used a TV control panel with 11 symbols in the matrix and a 2 × 2 light control panel for environmental control.…”
Section: Introductionmentioning
confidence: 91%
“…In our system, BOTAS can also be controlled using a hybrid BMI system with SSVEP and P300 (blue arrow procedure in Figure 1) (Sakurada et al, 2011). Our group previously used the so-called P300 speller (Farwell and Donchin, 1988) in a BMI system (Ikegami et al, 2011; Takano et al, 2011); we also included the P300 procedure in the BOTAS system. A monitor displays a flicker matrix and each flickering icon indicates a BOTAS motion that was recorded beforehand.…”
Section: Methodsmentioning
confidence: 99%